The Role of Public Enterprises in Economic Development in Nigeria - Anike, Happiness Ozioma Obi; Okafor, Chikodili Nkiruka; Udejinta, Nnaemeka Beneth (International Research Journal of Management, IT & Social Sciences, 2017)
The study focuses on the role of public enterprises in economic development in Nigeria.The study soughs to ascertain the role of public enterprises in improving theÂ  standard of living in Nigeria, to determine the nature of the relationship between Public enterprises and employment generation, to ascertain challenges encounter by public enterprises in contributing to national development .The study had a population size of 340, out of which a sample size of 246 was realised using Taro Yamaneâs formula at 5% error tolerance and 95% level of confidence. Instrument used for data collection was primarily questionnaire and interview...